Injury Surveillance during a European Touch Rugby Championship - Emma Cropper; Cari M. Thorpe; Simon Roberts; Craig Twist (MDPI AG, 2019)
Background: Touch (rugby/football) is a minimal contact sport for which the type and incidence of injuries remains unknown in Europe. Objectives: To establish the incidence, severity and nature of injuries sustained during a four-day European Touch Championship competition. Methods: A prospective cohort design was adopted to record match-related injuries during the European Touch Championships 2016. Injuries were collected from five countries and classified using the Orchard Sports Injury Classification (OSICS-10). Data were combined from all participating countries and injury incidence was recorded as number of injuries/1000 player hours. Results: A total of 135 injuries were recorded during the tournament with injury incidence calculated as 103.5 injuries per 1000 player match hours. Injuries were mainly recorded as transient (76%) occurring most frequently in the lower limb (69%). Injuries occurred more frequently on successive days, with exception to the final day of the tournament. The number of injuries was not different between the first and second half of matches and there was no relationship between the day of the tournament and the half of the match that injury occurred. Conclusion: Match injury incidence was 103.5 injuries per 100 player match hours. The most injured site was that of the lower limb, with the most common injury type reported as muscle/tendon injury. It is postulated that fatigue plays a role in injury incidence during a multiday tournament.